Identificação de genes diferencialmente expressos em amendoim, submetido a estresse hídrico - DUARTE, Elizabeth Amélia Alves (2008)
Peanut is a worldwide important product for food industries. In Brazil this crop is quite representative due its high consume. Most part of production is concentrated in the Southeast, Center-West and Northeast regions. In this last one, the wheather is a limiting factor for the crop; however, some botanical types present tolerance to prolonged dry conditions. The aim of this work was to identify genes differentially expressed in a peanut cultivar submitted to water stress which could aid on selective processes in the improvement programs carried out with this crop in the Northeast region. The cv. Senegal 55437 was chosen for this study due its recognizable tolerance to drought. It was submitted to five days of water stress under greenhouse conditions. The total RNA was collected from foliar tissues when plants reached 50% stomatic closure. RT-PCR assays were performed using ten ISSR primers and the c- DNAs obtained were re-amplified, purified and cloned into Escherichia coli, INFα cell (Invitrogen). A total of twenty-nine cDNA fragments were obtained, being seventeen at the down regulated condition, two at over regulated and ten activated. These later, only found in stressed samples, were sequenced. Sequences obtained were compared into databanks, focusing on Arabidobis thaliana and Arachis banks, andfour showed homology with genes which are involved in metabolic routes to abiotic and biotic factors. One of these sequences, with about 700pb, showed homology with Arabinogalactan protein 10 of A. thaliana. This structural protein present in the leaves, stems and roots is associated to regulatory processes initiated during the water loss by the cell, which genes increase protection to the cytoplasm, organelles,cell membranes, cellular osmotic potential alteration and improve better regulation in the expression of other genes. The result here obtained suggests a possible relation of this gene with the response routes to water stress.